Aberrant protein trafficking in retinal degeneration: The initial phase of retinal remodelling - Bales, Katie L. (Exp Eye Res, 2015)
Retinal trafficking proteins are involved in molecular assemblies that govern protein transport, orchestrate cellular events involved in cilia formation, regulate signal transduction, autophagy and endocytic trafficking, all of which if not properly controlled initiate retinal degeneration. Improper function and or trafficking of these proteins and molecular networks they are involved in cause a detrimental cascade of neural retinal remodeling due to cell death, resulting as devastating blinding diseases. A universal finding in retinal degenerative diseases is the profound detection of retinal remodeling, occurring as a phased modification of neural retinal function and structure, which begins at the molecular level. Retinal remodeling instigated by aberrant trafficking of proteins encompasses many forms of retinal degenerations, such as the diverse forms of retinitis pigmentosa (RP) and disorders that resemble RP through mutations in the rhodopsin gene, retinal ciliopathies, and some forms of glaucoma and age-related macular degeneration (AMD). As a large majority of genes associated with these different retinopathies are overlapping, it is imperative to understand their underlying molecular mechanisms. This review will discuss some of the most recent discoveries in vertebrate retinal remodeling and retinal degenerations caused by protein mistrafficking.